Taking the P in political corporate social responsibility seriously - Wickert, Christopher; van Witteloostuijn, Arjen (Journal of International Business Studies, 2023)
In this commentary, we engage with the study by Carney, El Ghoul, Guedhami, Lu and Wang, titled “Political corporate social responsibility: The role of deliberative capacity.” Their study provides empirical support for earlier claims that deliberative capacity – the capacity of political institutions to enable diverse stakeholders to collectively assemble and voice their opinions – is an important building block to understanding the prominence or lack thereof of corporate social responsibility (CSR) in a country. In so doing, Carney and co-authors contribute to the so-called “Political CSR” or PCSR literature. Yet, their study carries two important shortcomings that can be addressed to bring PCSR research forward in an IB context. First, they ignore a fundamental tenet of the PCSR literature, namely the existence of global governance gaps requiring private businesses to actively engage in political activity. Second, and related to the first, their model and associated variables are misspecified, with independent and dependent variables that are at least partially overlapping. Departing from these shortcomings, we attempt to engage constructively with their work in the interest of advancing the conversation in IB about private sector involvement in democratic will formation to achieve social and environmental responsibility.